(untitled) (Revista Paradigma, 2020)
This study analyzes the directions for contemporary education and how they affect the lives of the subjects, having as scope the research developed by the North American philosopher Martha Nussbaum. The justification for this is reflected in the fact that certain areas of knowledge are being neglected by a strictly economic approach. To this end, we question the ways to prevent the disappearance of humanitarian education, since it can contribute to the creation of a society capable of promoting the development of human capacities and a minimally decent life project. For its delineation, the research makes use of the hypothetical-deductive approach method, centered in the bibliographical research, having as source contemporary authors in the area of the political philosophy. Understanding the silent democratic crisis, which affects the countries of the globe and is shaped by an education for profit rather than democracy, presents a challenge. With Nussbaum, we conclude that the soundness of a democratic system effectively depends on human capabilities. Economic development does not necessarily guarantee subjects’ quality of life and social justice, since income and wealth are not directly related to human progress. A democratic and citizen education that enables human emancipation through critical thinking, which promotes compassion and empathy, would necessarily involve the teaching of the humanities and the arts.